Student experiences and effectiveness of project-based learning in an organic practicum chalcone synthesis experiments - Nova Yunita Putri Olii; Muhammad Choirul; Indriana Tasya; Sri Lestari; Agung Rahmadani (Universitas Muhammadiyah Malang, 2024)
Practicum serves as the main support for organic chemistry learning, enhancing both conceptual comperand strengthening students' practical skills through learning experiences. The purpose of this study is to analyze students' learning experiences and the effectiveness of project-based learning (PjBL) in organic chemistry practicum on chalcone synthesis experiment. This study used a mixed method that included both quantitative and qualitative data. The study's findings indicate that project-based learning significantly improves student learning outcomes, as evidenced by an N-Gain of 0.92 and a presentase of 91.97%, as well as an effect size that indicates a significant impact of project-based learning on student learning outcomes. Qualitative data from student surveys also indicated that PjBL not only improved understanding and practical skills, but also added fun to the learning process. This research confirms the importance of innovation in teaching methods to improve student engagement and learning outcomes.